On uniform dichotomy in mean of stochastic skew-evolution semiflows in Banach spaces - Fülöp Tímea Melinda Személy (Annals of the West University of Timisoara: Mathematics and Computer Science, 2023)
In this paper we consider three concepts of uniform dichotomy in mean for stochastic skew-evolution semiflows: uniform exponential dichotomy in mean, uniform polynomial dichotomy in mean and uniform h- dichotomy in mean. Some characterizations of these notions and connections between these concepts are given. The obtained results can be considered generalizations to the dichotomy case of the results from [29].